The Relationship Between Madrasah Head Supervision And Work Motivation On The Pedagogical Competence Of Public Madrasah Tsanawiyah Teachers In Asahan Regency - Mhd Armawi Fauzi; Makmur Syukri; Yusuf Hadijaya (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
This research was conducted because teachers at the State Madrasah Tsanawiyah in Asahan rarely prepare lesson plans (RPP), are less active in conducting assessments, do not develop learning materials, and do not optimally explore student potential. In addition, there are problems related to teachers' low work motivation. Supervision conducted by the madrasah head is not very effective, because only a small proportion of teachers are supervised. The research method used in this study is a quantitative descriptive type of correlational study with a correlative study pattern by placing the research variables into two groups, namely the independent variable and the dependent variable Before the research questionnaire is used to obtain data, content validity is first carried out, then tested to see the validity and reliability of the questionnaire. To test the validity, namely by calculating the correlation coefficient (r) of the item with the total score. The item is said to be valid (valid) if the correlation value (r) > the critical price of r product moment with a significant level of 5%. There is a significant relationship between madrasah head supervision and teacher pedagogical competence. This confirms the important role of supervision carried out by madrasah principals in improving teachers' pedagogical competence. The support, guidance and direction provided through supervision are proven to contribute positively to the improvement of teachers' pedagogical skills, which in turn can improve teachers' pedagogical competence.